Using Creative Learning Methods through Letter Cards to Improve the Qur'an Reading Skill at Tadika Al Fikh Orchard Pendamar Indah Malaysia - Indah, Yuli; Pasaribu, Munawir (Journal of English Language and Education, 2025)
Researchers study low understanding and reading skills of the Qoran among students at Tadika Al-Fikh Orchard. One of the contributing factors is that traditional teaching methods are less interesting, so children are less motivated to recognize and understand hijaiyah letters and analyze the effectiveness of using creative learning methods with hijaiyah letters in improving students' abilities at Tadika al fikh orchard in understanding the Qur'an. This teaching approach aims to provide interesting, motivating learning strategies and improve children's understanding of the hijaiyah letters. Using an experimental design, this study involved seven Tadika students. Data analysis used descriptive statistics to measure the increase in the ability to read the Qur'an. According to the research findings, creative teaching methods that combine hijaiyah letters significantly improve students' ability to understand the Qur'an when compared to traditional teaching methods. It is hoped that all of this will contribute to the development of educational strategies in Islamic educational environments.